Lithuanian Gays and Lesbians’ Coming Out in the Public/Private Divide: Sexual Citizenship, Secrecy and Heteronormative Public - Tereškinas, Artūras (Sociologija. Mintis ir veiksmas, 2007)
The paper focuses on the relationship between Lithuanian gays and lesbians’ coming out experiences and sexual citizenship. Analyzing Lithuanian homosexuals’ view of public/private divide, it asks how they perform their identities in public and private settings and how they align themselves with being public. What anxieties over citizenship and sexual boundaries are reflected in their life histories? The paper starts from the premise that “sexual citizenship” can be considered a fourth aspect of citizenship in addition to the traditional model of political, social and civic rights. Plummer (1995) conceptualizes it as rights to choose what people do with their bodies, emotions, relationships, gender identities and desires. This citizenship is related to the plurality of multiple and overlapping public discourses on intimacies. Diane Richardson (2000a) emphasizes the “right of identity” as a part of sexual citizenship. This right to have a public identity is particularly relevant when we speak of wider issues of secrecy and disclosure, discrimination and tolerance, and the private and public. Examining 32 interviews with gays and lesbians, in this paper, we argue that their life stories comprise the context for the emergence of the sexual citizen because these stories tell of exclusion based on sexuality, gender, body, and publicity in the post-Soviet Lithuania. Since the public is still exclusive of homosexuality, most interviewed homosexuals attempt to pass as heterosexual in the public sphere. In a society in which heteronormativity is a powerful principle of social and cultural order and heterosexuality, an essential aspect of human nature and intelligibility, the majority of homosexual people hide their sexual orientation from their relatives, colleagues and even friends. The informants’ lives oscillate between pleasure to be open and danger to be stigmatized. On one hand, they strive for greater integration of their sexual experiences into cultural narratives of citizenship; on the other hand, absorbing normative sexual and gender disciplines they succumb to conservative appeals to privatized sexual identities.